JEOMANYETİK İNDİSLER İLE SCHUMANN REZONANS FREKANSLARI ARASINDAKİ İLİŞKİNİN İNCELENMESİ - ÖREN, TOLGA (Fırat Üniveristesi, 2018)
Bu çalışmada Schumann rezonans frekansları ile jeomanyetik indisler (Dst ve Kp) aralarındaki ilişki istatistiksel olarak incelenmiştir. Schumann rezonans frekanslarının 2016 yılı ilk beş ayı ( Ocak, Şubat ,Mart, Nisan, Mayıs) verileri ile saatlik ortalama Dst ve üç saatlik ortalama Kp değerleri arasındaki ilişki ayrı ayrı tanımlayıcı istatistik ve regresyon modeli uygulanarak belirlenmiştir. Yapılan inceleme sonucunda Schumann rezonansının özellikle 21 Hz'e yakın olan frekansı ile Dst'nin tüm seti arasında pozitif yönde ilişkide olduğu görülmüştür. Ayrıca Dst ve Dst yönlerinin 14 Hz, 21 Hz ve 28 Hz frekansları ile de ilişkili olduğu, ancak 7 Hz ve 35 Hz frekans değerleri ile Dst arasında ilişki olmadığı belirlenmiştir. Bu frekans değerleri için Dst'nin yönleriyle elde edilen açıklanabilirlilik oranları sırasıyla 0.31, 0.28 ve 0.32 olarak hesaplanmıştır. Schumann rezonansının 7 Hz ve 21 Hz'e yakın olan frekansı ile Kp arasında pozitif yönde ilişkili olduğu diğer frekanslar 14 Hz, 28 Hz ve 35 Hz ilişkili olmadığı elde edilmiştir. 7 Hz ve 21 Hz lik Schumann frekansları ile Kp arasındaki açıklanabilirlilik oranları sırasıyla 0.38 ve 0.27 olarak hesaplanmıştır. Anahtar Kelimeler: Schumann Rezonans Frekansları, Dst, Kp, Tanımlayıcı İstatistik, Regresyon Analizi

In this study, it has been statistically investigated the connections between Schumann resonance frequencies and geomagnetic indices Dst and Kp. The relations between the Schumann resonance frequencies data given in the first five months of 2016 (January, February, March, April, May) and the data of average Dst value measured for one hour and Kp for three hour have been determined by applying descriptive and regression statistical models separately. According to the results of the statistical analyses it has been proved that there is a positive way relation between the Schumann resonance frequency (especially the one nearest to 21 Hz) and all the set of Dst. The frequencies of 14 Hz, 21 Hz and 28 Hz were also connected with the directions of Dst but no any connection between the frequencies of 7 Hz and 35 Hz and Dst has been identified. The explainable rates for these frequency values obtained by using the directions of Dst have been found out as 0.31, 0.28, 0.32 respectively. It has been obtained that there is a positive correlation between the Schumann resonance frequencies of the nearest to 7 hz and 21 Hz and Kp, but no connection with the other frequencies of 14 Hz, 28 Hz and 35 Hz. The explainable rates of the correlation between 7 Hz and 21 Hz of Schumann resonance frequencies and Kp have been calculated as 0.38 and 0.27 respectively. Keywords: Schumann resonance frequencies, Dst, Kp, Descriptive statistics, Regression snalysis
The investigation of the relationship between geomagnetic indices and schumann resonance frequences
Keywords: Fizik ve Fizik Mühendisliği